Insight into the Bouguer-Beer-Lambert Law: A review - Moses Kayanda Kiteto; Cleophas Achisa Mecha (Sustainable Chemical Engineering, 2024)
The Bouguer-Beer-Lambert law, a fundamental principle in spectroscopy that establishes a linear relationship between absorbance and concentration, has been indispensable for chemical analysis and quantitative measurements. Its elegant simplicity and robust utility have enabled the determination of solute concentrations in various solutions, leading to applications across diverse scientific disciplines. However, the inherent assumptions and limitations of this law have resulted in deviations, mostly fundamental, chemical, and instrumental, which have inspired a fervent pursuit of modifications aimed at enhancing its accuracy and expanding its scope. This review aims to shed light on the ongoing quest for its modification, providing an in-depth analysis of the law and delving into its historical overview, from the work of Pierre Bouguer to the modern formulation. Moreover, the classical and electromagnetic formulations of the law have been thoroughly studied, and a comprehensive overview of the law's limitations is presented. Furthermore, some of the major modifications that have been made in attempts to expand its reach across different realms are evaluated. Advanced approaches toward generalized modification of the law have also been extensively discussed. Finally, the review addresses the challenges in formulating a generalized Bouguer-Beer-Lambert law and proposes possible solutions and future directions that should be taken to improve the accuracy and wide applicability of the law.